59 LONG-TERM OUTCOMES OF SINGLE VERSUS MULTIVESSEL STENTING IN A PUBLIC HEALTH SYSTEM PATIENT POPULATION, WITH UNIFORM BARE METAL STENT SELECTION, ADJUNCTIVE GLYCOPROTEIN IIB/IIIA INHIBITION AND LONG-TERM CLOPIDOGREL THERAPY. (1st January 2005) - Nathan, S.; Attanasio, S.; Amin, A.; Kumar, A.; Gupta, A.; Kelly, R. F.
Abstract : Background: It has been suggested that lower socioeconomic status may adversely impact health outcomes. Data regarding post-PCI outcomes are particularly limited in this population. We assessed event-free survival in public health system (PHS) patients undergoing single (SV) vs multivessel (MV) PCI with intended stent deployment, GpIIb/IIIa inhibition and long-term clopidogrel therapy. Methods: 290 consecutive patients (212 SV, 78 MV) undergoing PCI at Cook County Hospital, with uniform Medtronic AVE bare metal stent use, procedural GPIIb/IIIa inhibition and intended long-term clopidogrel were followed as a prospective cohort for occurrence of a composite MACE end point (death, MI, urgent TVR) and all-cause mortality. Results: Demographic variables and risk factors were similar between SV and MV groups except smoking (80.6% vs 19.4%, p < .031) and family history of CAD (65.2% vs 34.8%, p = .02). PCI indications were comparably distributed. 46% of patients overall presented with ACS/NSTEMI or STEMI. GPIIb/IIIa inhibition was used in 98.3% of patients and 86.1% of patients were on aspirin plus clopidogrel at followup. The groups were similar with regard to stents per vessel and stented length per vessel but differed by total stents per patient (1.05 vs 1.79, p < .001). Clinical follow-up (mean 213, maximum 622 days) was attained in 90% of patients. MACE-free survival by Kaplan-Meier analysis was similar at 180 days (98.8% vs 93.2%, p = .15) and 360 days (96.6% vs 90.4%, p = .19). Overall 1 year survival was 94.8%. Conclusions: Single and multivessel PCI with adjunctive Gp2b3a inhibition and long-term clopidogrel therapy was associated with excellent event-free survival in the PHS population studied. Despite a large proportion of high-risk patients, these estimates are comparable to historical, non-PHS control populations undergoing bare metal stenting.